The Influence of Digital Payment on Generation Z Consumer Behavior in the Karang Taruna Community of the Jagakarsa Area, South Jakarta - Nisya Kartiko Dewi; Trisni Handayani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, digital payment is utilized as an efficient, secure, and rational transaction instrument to support economic activities, particularly among Generation Z, who are widely recognized for their adaptability to digital technology. However, in practice, the ease and intensity of digital payment usage may influence consumer behavior, including increased transaction frequency and changes in consumers’ decision-making patterns. This study aims to examine the effect of digital payment on the consumer behavior of Generation Z within the Karang Taruna community in the Jagakarsa area, South Jakarta. This study employs a field research design with a quantitative approach using a survey method. Primary data were collected through structured questionnaires distributed to 69 Generation Z respondents, while secondary data were obtained from relevant scholarly literature. Data analysis was conducted using validity and reliability tests, classical assumption tests, simple linear regression analysis, and t-tests. The findings indicate that digital payment has a positive and significant effect on the consumer behavior of Generation Z. These results suggest that digital payment functions not merely as a transactional tool but also as a factor that shapes consumption patterns and behavioral dynamics within a social community context.